THU0092 The advantage of early intervention by tocilizumab for rheumatoid arthritis - full analysis of all-case postmarketing surveillance in 7, 901 patients in japan. (23rd January 2014) - Yamanaka, H.; Harigai, M.; Inokuma, S.; Ishiguro, N.; Ryu, J.; Takei, S.; Takeuchi, T.; Tanaka, Y.; Sano, Y.; Koike, T.
Abstract : Background: Tocilizumab (TCZ), a humanized anti-human interleukin-6 receptor monoclonal antibody, has been approved worldwide for rheumatoid arthritis (RA), and an all-case postmarketing surveillance (PMS) program was conducted in Japan. Objectives: The aim of this surveillance is to investigate the safety and effectiveness of TCZ for the treatment of rheumatoid arthritis (RA) in the daily clinical setting. Methods: This full analysis report includes 7, 901 patients who received TCZ at a dose of 8 mg/kg every 4 weeks, and were observed for 28 weeks. Results: Baseline characteristics included: mean age 58.7 years old (≥70 years in 20.7%); mean disease duration 10.4 years (≥10 years in 37.6%); previous TNF inhibitor use in 62.6%, concomitant methotrexate (MTX) use in 55.8% and concomitant glucocorticoid use in 74.0%. The mean DAS28-ESR improved from 5.5 at baseline to 2.9 at week 28 (LOCF method) with TCZ treatment; 47.6% of patients achieved DAS28 remission (DAS28-ESR <2.6), and 15.1% of patients achieved Boolean remission. The DAS28 remission rate and Boolean remission rate were significantly higher in patients whose disease duration was <2 years than in patients whose disease duration was ≥10 years (p<0.0001, χ 2 test). Same results were obtained irrespective of the previous use of TNF inhibitor (p<0.0001 for both remission criteria in both TNF inhibitor-naïve and TNF inhibitor-used patients). However, TNF inhibitor-naïve patients showed significantly better response than the TNF inhibitor-used patients (p<0.0001, χ 2 test). The incidence rates of all adverse events and serious adverse events (AEs and SAEs) were 43.9% and 9.6%, respectively. The incidence rate of SAEs was significantly lower in patients whose disease duration was <2 years (p<0.0001, χ 2 test, vs. ≥10 years). Infections were the most frequent AE (11.1%) and SAE (3.8%). The incidence rates of infections and serious infections were significantly lower in the patients whose disease duration was <2 years (p<0.0001, χ 2 test, vs.≥10 years). Similar results were observed when comparing the incidence of serious respiratory infections, which are the most common site-specific infection and serious infection, by disease duration. Conclusions: Theseresults demonstratedthat treatment with TCZ was effective and well-tolerated in Japanese RA patients in the daily clinical setting, and also suggested that TCZ can be used more effectively and safely in anti-TNF naïve RA patients with shorterdisease duration than in patients with established disease. Disclosure of Interest: H. Yamanaka Grant/Research support from: Abbott, Bristol-Myers Squibb, Chugai, Janssen, Eisai, Mitsubishi-Tanabe, Otsuka, Takeda, Pfizer, Consultant for: Abbott, Bristol-Myers Squibb, Chugai, Hoffmann-La Roche, Janssen, Eisai, Mitsubishi-Tanabe, Otsuka, Takeda, Pfizer, M. Harigai Grant/Research support from: Abbott Japan Co. Ltd., Bristol-Myers Japan, Chugai Pharmaceutical Co. Ltd., Eisai Co. Ltd., Mitsubishi Tanabe Pharma Corp., Pfizer Japan Inc., Takeda Pharmaceutical Co. Ltd., Consultant for: Abbott Japan Co. Ltd., Chugai Pharmaceutical Company, Janssen Pharmaceutical KK, Mitsubishi Tanabe Pharma Corp, S. Inokuma: None Declared, N. Ishiguro Grant/Research support from: Abbott Japan Co. Ltd., Bristol-Myers Japan, Chugai Pharmaceutical Co. Ltd., Eisai Co. Ltd., Mitsubishi Tanabe Pharma Corp., Pfizer Japan Inc., Takeda Pharmaceutical Co. Ltd., Speakers Bureau: Chugai, Eisai, Astellas, Mitsubishi-Tanabe, Takeda, J. Ryu: None Declared, S. Takei: None Declared, T. Takeuchi Consultant for: Abbott Immunology Pharmaceuticals, AstraZeneca, Bristol-Myers Squibb, Chugai, Astellas, Mitsubishi-Tanabe, Pfizer, Takeda, Y. Tanaka Consultant for: Abbott Immunology Pharmaceuticals, Chugai, Eisai, Astellas, Mitsubishi-Tanabe, Takeda, Y. Sano Employee of: Chugai, T. Koike Consultant for: Abbott Immunology Pharmaceuticals, Bristol-Myers Squibb, Astellas, Otsuka, Speakers Bureau: Abbott Immunology Pharmaceuticals, Chugai, Eisai, Mitsubishi-Tanabe, Takeda, Pfizer